"Sailing to Utopia" - Ruth Nestvold (b. 1958) (Flytrap, 2006)
Flawed utopias. A woman travels to New Boston (Bellamy’s future), Gilman’s Herland, and More’s Utopia and finds them less than utopian.
Keywords: Female author; US author